Does Cognitive Load Influence Moral Judgments? The Role of Action–Omission and Collective Interests - Mufan Zheng; Liying Wang; Yueying Tian (Behavioral Sciences)
This study aimed to investigate the impact of cognitive load on moral judgments while incorporating action propensities and collective interests as variables. Study 1 (N = 102) used the dot matrix memory task to manipulate cognitive load, and participants made moral choices in action dilemmas and omission dilemmas. The findings revealed that when confronted with action moral dilemmas, participants in the high-cognitive load group exhibited a greater inclination towards utilitarian responses compared to those in the low-load group. However, cognitive load did not affect utilitarian choices in omission moral dilemmas. Study 2 (N = 100) further introduced the identities of protagonists in dilemmas involving conflicts between collective and individual interests. When facing a collective–individual interest conflict, participants under high cognitive load were more inclined to prioritize collective interests over individual interests compared to those under low load. Additionally, participants were more likely to choose collective interests in omission moral dilemmas than in action dilemmas. The impact of cognitive load on moral judgments was also influenced by the identities of the protagonists.